2009
DOI: 10.1002/path.2653
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic NRF2 mutations in squamous cell carcinomas of oesophagus and skin

Abstract: Nuclear factor erythroid-related factor 2 (NRF2) encodes a transcription factor that induces expression of cytoprotective proteins upon oxidative stress and oncogenic NRF2 mutations have been found in lung and head/neck cancers that inactivate KEAP1-mediated degradation of NRF2. The aim of this study was to catalogue NRF2 mutations in other human cancers. For this, we analysed 1145 cancer tissues from carcinomas from oesophagus, skin, uterine cervix, lung, larynx, breast, colon, stomach, liver, prostate, urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
266
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(278 citation statements)
references
References 28 publications
8
266
2
2
Order By: Relevance
“…Somatic mutations in the coding region of Nrf2 that allow Nrf2 to escape repression by the Keap1-Cullin3 E3 ubiquitin ligase were found in lung (11/103; 10.7%) and head and neck (3/12, 10.7%) tumors (25). In a similar study, Nrf2 mutations were found in esophagus (8/70; 11.4%), skin (1/17; 6.3%), lung (10/125; 8.0%), and larynx (3/23; 13.0%) tumors (26). More recently, we have reported a study on Nrf2 expression in endometrial cancer patients (117 cases).…”
supporting
confidence: 49%
“…Somatic mutations in the coding region of Nrf2 that allow Nrf2 to escape repression by the Keap1-Cullin3 E3 ubiquitin ligase were found in lung (11/103; 10.7%) and head and neck (3/12, 10.7%) tumors (25). In a similar study, Nrf2 mutations were found in esophagus (8/70; 11.4%), skin (1/17; 6.3%), lung (10/125; 8.0%), and larynx (3/23; 13.0%) tumors (26). More recently, we have reported a study on Nrf2 expression in endometrial cancer patients (117 cases).…”
supporting
confidence: 49%
“…The proteins encoded by these mRNAs control various pathways, and their potential roles in cancer are particularly intriguing. This is important with regard to the enhanced activity of NRF2 in various types of human cancer 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…This activity is very important in the skin, where loss of Nrf2 or its functional inhibition prolonged the inflammatory response after wounding 3 and enhanced the susceptibility to chemically induced carcinogenesis 4,5 . On the other hand, Nrf2 is activated in a variety of human cancers 6 , including cutaneous squamous cell carcinomas 7 , and activation of Nrf2 correlates with increased tumour aggressiveness 4,8 . Furthermore, we recently showed that pharmacological or genetic activation of Nrf2 in keratinocytes of mouse skin severely affects the cornified enveloping, resulting in the development of an ichthyosis-like skin disease that is characterized by acanthosis, hyperkeratosis and impaired barrier function 9 .…”
mentioning
confidence: 99%
“…[3][4][5] In cancer, NRF2 activation is pro-tumoural in a spectrum of malignancies through mutations in NRF2 or its cytosolic inhibitor KEAP1. [6][7][8][9] However, we have previously shown that in human AML constitutive activation of the NRF2 signalling pathway is not through somatic mutations of NRF2/Keap1 but as a consequence of upstream constitutive activation by NF-κB. 10,11 In addition to contributing to the malignant phenotype of AML, we also found that NRF2 contributes to intrinsic leukaemia cell resistance to standard front-line chemotherapy agents.…”
mentioning
confidence: 94%